83. Isoelectric electroencephalogram as early marker of poor prognosis: A case report. Issue 4 (April 2016) - Frigeni, B.; Ferri, F.; Foresti, C.; Quadri, S.; Venturelli, E.
Abstract : Isoelectric electroencephalogram (EEG) in conformant with clinical findings is one of the criteria of brain death. In clinical practice, isoelectric EEG is rarely seen in patients who are not brain-dead. We present a case of a 66-year-old woman with headache and acute confusional state. Brain TC showed aneurysmal subarachnoid hemorrhage for the rupture of anterior communicating artery aneurysm. During anesthesia and intubation patient presented acute anisocoria. Brain CT showed rebleeding with subarachnoid blood in anterior interhemispheric cistern and intraventricular.Serial EEG were flat and somatosensory evoked potentials demonstrated absent waves at the cortical level but there was evidence of preserved cerebral blood flow on computed tomography angiography. Her neurological examination continued to show evidence of residual brainstem function (cranial nerve reflexes and coughing). He survived this condition for 5 days and afterward every criteria for brain death could be applied.EEG records activity from only the cortical layers immediately beneath the scalp; it does not record from subcortical structures but EEG can be a very early marker of diffuse cortical damage. This case demonstrates that isoelectric EEG can not be equated with brain death but can be a very early marker of poor prognosis.